Physical activity programmes for patients undergoing neo-adjuvant chemoradiotherapy for rectal cancer: A systematic review and meta-analysis. Issue 51 (23rd December 2021) - Latrille, Marianne; Buchs, Nicolas C.; Ris, Frédéric; Koessler, Thibaud
Abstract : Supplemental Digital Content is available in the text Abstract: Background: Patients diagnosed with localized rectal cancer should undergo Neoadjuvant Radio-Chemotherapy (NACRT) followed, a few weeks later, by surgical resection. NACRT is known to cause significant decline in the physical and psychological health of patients. This literature review aims to summarize the effects of a prehabilitation programme during and/or after NACRT but before surgery. Methods: Articles included in this review have been selected by two independent researchers on Pubmed, Google Scholar, and Cochrane databases with the following terms: "Rectal Cancer AND Physical Activity" and "Exercise AND Rectal Cancer." Results: We obtained 560 articles. We selected 12 of these, representing 7 series but only one randomized study, constituting 153 patients in total. Most studies included have considerable variation in their prehabilitation programmes, in terms of supervision, training content, frequency, intensity, duration, and temporality, in regard to NACRT and surgery. Implementing a prehabilitation programme during NACRT seems feasible and safe, with adherence ranging from 58% to 100%. VO2max (maximal oxygen consumption during incremental exercise) was improved in three of the studies during the prehabilitation programme. No significant difference in the step count, 6-minute-walk test, or quality of life was seen. Conclusions: Prehabilitation programmes during NACRT for localized rectal cancer patients are safe and feasible; however, due to considerable variation in the prehabilitation programmes and their small size, impact on fitness, quality of life, and surgical outcome are unknown. Larger randomized studies are needed.